Radio speech resources applicable in outreach communication in archeology - San Martín González, Francisco Javier (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Museums have lost visitors as a result of COVID-19 and the public continues to believe that science is boring. In this context of crisis, we examine, through content analysis techniques, the presence of archeology in radio programs and we study the linguistic resources that make communication capable of exciting, improving the chances of success of scientific dissemination. We conclude that the shortage of qualified human resources in communication of science and expert in resources to make it more attractive can endanger the recovery of museums as centers of leisure, culture and knowledge.